Nuclear Inositide Signaling Via Phospholipase C. Issue 8 (25th April 2017) - Ratti, Stefano; Mongiorgi, Sara; Ramazzotti, Giulia; Follo, Matilde Y.; Mariani, Giulia A.; Suh, Pann‐Ghill; McCubrey, James A.; Cocco, Lucio; Manzoli, Lucia
ABSTRACT: The existence of an independent nuclear inositide pathway distinct from the cytoplasmic one has been demonstrated in different physiological systems and in diseases. In this prospect we analyze the role of PI‐PLCβ1 nuclear isoform in relation to the cell cycle regulation, the cell differentiation, and different physiopathological pathways focusing on the importance of the nuclear localization from both molecular and clinical point of view. PI‐PLCβ1 is essential for G1/S transition through DAG and Cyclin D3 and plays also a central role in G2/M progression through Cyclin B1 and PKCα. In the differentiation process of C2C12 cells PI‐PLCβ1 increases in both myogenic differentiation and osteogenic differentiation. PI‐PLCβ1 and Cyclin D3 reduction has been observed in Myotonic Dystrophy (DM) suggesting a pivotal role of these enzymes in DM physiopathology. PI‐PLCβ1 is also involved in adipogenesis through a double phase mechanism. Moreover, PI‐PLCβ1 plays a key role in the normal hematopoietic differentiation where it seems to decrease in erythroid differentiation and increase in myeloid differentiation. In Myelodysplastic Syndromes (MDS) PI‐PLCβ1 has a genetic and epigenetic relevance and it is related to MDS patients' risk of Acute Myeloid Leukemia (AML) evolution. In MDS patients PI‐PLCβ1 seems to be also a therapeutic predictive outcome marker. In the central nervous system, PI‐PLCβ1 seems to be involved in different pathways in both brain cortex development and synaptic plasticity related to different diseases. Another PI‐PLC isozyme that could be related to nuclear activities is PI‐PLCζ that is involved in infertility processes. J. Cell. Biochem. 118: 1969–1978, 2017. © 2017 Wiley Periodicals, Inc. Abstract : The existence of an independent nuclear inositide pathway distinct from the cytoplasmic one has been demonstrated in different physiological systems and in diseases. In this prospect we analyze the role of PI‐PLCβ1 nuclear isoform in relation to the cell cycle regulation, the cell differentiation, and different physiopathological pathways focusing on the importance of the nuclear localization from both molecular and clinical point of view.